Penalty kick outcomes in UEFA club competitions (2010-2015): The roles of situational, individual and performance factors - Almeida, C. H.; Volossovitch, A.; Duarte, R. (International Journal of Performance Analysis in Sport, 2016)
This study aimed to investigate main and interaction effects of situational (competition phase, match location, match status and match period), individual (penalty taker's footedness, playing position, and age difference to the goalkeeper), and performance factors (shot direction and goalkeeper's action) on penalty kick outcome in UEFA Champions and Europa leagues. Data were collected from soccer Internet sites and TV broadcasts during five consecutive seasons (from 2010-2011 to 2014-2015). A total of 536 penalties were recorded and analysed considering the aforementioned three groups of variables and the respective penalty outcome (goal, saved or missed). Multinomial logistic regression analysis was used to assess the effects of factors on penalty outcome. The logistic regression model revealed the probabilities of penalty kicks being saved significantly increased (1) in the middle of matches (30:01-60:00) and (2) when the shots were directed to lower zones of the goal, in particular to the lower centre-left zone of the goal (penalty taker's perspective). Besides, the odds of missing the penalty substantially increased when the shot aimed the high zones of the goal. Based on the current findings, penalty takers should be encouraged to direct the shot to the upper corners of the goal and goalkeepers should wait longer in order to dive to the correct side of the ball. Although performance factors were the most decisive for determining the penalty outcome, situational factors such as match period may also influence the success of penalty kicks.